A REVIEW ON PATIENT-CONTROLLED ANALGESIA INFUSION SYSTEM - Shola, Usha Rani; V, Neela Narayanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
PCA is a patient-controlled analgesia infusion pump, which is used to infuse the medicine into the patients after surgery. It contains a syringe with painÂ medicine to infuse that is prescribed by the physician. The drugs used for pain control are high-alert medicines, since overmedication may cause deathÂ to the patients. These types of unbearable events may happen due to medical errors, prescription errors, adverse events (AEs), etc. Hence, it requiresÂ a precautionary attention or continuous monitoring for PCA pump infusion patients. However, always physicians or nurses may not monitor a patientÂ continuously. To provide safety to the patient, the PCA pump needs a smart care process to alert the physician. This study represents the survey onÂ PCA pump errors, AEs, and solutions for it to avoid them. The solution will automatically alert the infusion-related situation of the patients, those areÂ taking the intravenous drug infusion at different procedure rooms in the hospitals. Moreover, it increases the safety to infusion pump with advancesÂ of decision-making in health, patient monitoring, alert notification to nursing, and productivity. This quality care can be achieved by integrating theÂ PCA pump with other intelligent systems. Â Â